1999
DOI: 10.1016/s0006-3495(99)77317-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Induced Polymerization of Actin

Abstract: Living cells contain a very large amount of membrane surface area, which potentially influences the direction, the kinetics, and the localization of biochemical reactions. This paper quantitatively evaluates the possibility that a lipid monolayer can adsorb actin from a nonpolymerizing solution, induce its polymerization, and form a 2D network of individual actin filaments, in conditions that forbid bulk polymerization. G- and F-actin solutions were studied beneath saturated Langmuir monolayers containing phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 38 publications
5
61
2
Order By: Relevance
“…We suggest that during the interaction proteins act as centres of condensation for monomeric (H + ) 2 TPPS 4 species, thus facilitating the formation of J-aggregates on the surface of protein moiety. Similar surface-induced polymerization processes were reported for monomeric actin on a positively charged lipid monolayer [18]. High concentration of BSA disrupts these aggregates forming the protein-porphyrin complex absorbing at 421 nm.…”
Section: Discussionsupporting
confidence: 76%
“…We suggest that during the interaction proteins act as centres of condensation for monomeric (H + ) 2 TPPS 4 species, thus facilitating the formation of J-aggregates on the surface of protein moiety. Similar surface-induced polymerization processes were reported for monomeric actin on a positively charged lipid monolayer [18]. High concentration of BSA disrupts these aggregates forming the protein-porphyrin complex absorbing at 421 nm.…”
Section: Discussionsupporting
confidence: 76%
“…This was demonstrated for the lipid-induced polymerization of actin (Renault et al, 1999). More specifically, it was found that chemically identical lipid surfaces behave differently when present as monolayers or liposomal bilayers.…”
Section: Membrane As a Template For Protein Aggregationmentioning
confidence: 79%
“…The mechanisms of surface-induced fibrillization may be fundamentally different from that occuring in bulk solution because of the restrictions imposed by the dimensionality of the system and the physicochemical and dynamic properties of the surface (Zhu et al, 2002(Zhu et al, , 2004Renault et al, 1999). This was demonstrated for the lipid-induced polymerization of actin (Renault et al, 1999).…”
Section: Membrane As a Template For Protein Aggregationmentioning
confidence: 99%
“…Actin is an anionic protein that has been shown to interact with charged lipids, in both the monomeric (G-actin) and polymeric (F-actin) forms (53). Additionally, liposomes have been shown to induce G-actin to form F-actin, a process that is charge-dependent (54).…”
Section: Biophysical Journal 108(8) 1946-1953mentioning
confidence: 99%